Oral Health İn Cleft Lip And Alveolus - S. Burçak Cengiz; Defne Keçik; Meryem Tekçiçek; Ayhan Enacar (Galenos Yayinevi, 2004)
Cleft lip and palate is one of the most common congenital deformities. Patients who have clefts of the lip and palate often need complex and extensive treatment, usually provided by an interdisciplinary team of pediatrists, orthodontists, plastic surgeons, pediatric dentists, maxillofacial surgeons, speech therapists, and others. In this paper, dental anomailes that usually occur in the children with cleft lip and palate will be discussed as well as the increased caries incidence and need for preventive programs in the same population.